2006
DOI: 10.1186/1471-2318-6-18
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the feasibility of a community-based strength training program for older people with depressive symptoms and its impact on depressive symptoms

Abstract: Background: Depression is a disabling, prevalent condition. Physical activity programs may assist depression management in older people, ameliorate co-morbid conditions and reduce the need for antidepressants. The UPLIFT pilot study assessed the feasibility of older depressed people attending a community-based progressive resistance training (PRT) program. The study also aimed to determine whether PRT improves depressive status in older depressed patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
2
11

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(94 citation statements)
references
References 34 publications
(34 reference statements)
2
75
2
11
Order By: Relevance
“…Eleven studies were included in the second group, which examined the effect of strength training on affect [17,18,20,29,49,57,[65][66][67][68]74], and 15 studies on non-specific physical activity or mindful activities such as yoga or Tai Chi were included in the third group [4,7,8,10,15,16,18,30,40,47,41,56,58,75,77]. One study [57] compared aerobic and resistance training to a control group in reducing depression and thus was included in both the first and second group.…”
Section: Review Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven studies were included in the second group, which examined the effect of strength training on affect [17,18,20,29,49,57,[65][66][67][68]74], and 15 studies on non-specific physical activity or mindful activities such as yoga or Tai Chi were included in the third group [4,7,8,10,15,16,18,30,40,47,41,56,58,75,77]. One study [57] compared aerobic and resistance training to a control group in reducing depression and thus was included in both the first and second group.…”
Section: Review Of the Studiesmentioning
confidence: 99%
“…One study [20] did not report any emotional alterations following 8 weeks of resistance training. Of the four studies which did not assess strength improvement, one study [67] reported alleviation in depression, and another one [65] reported partial improvement in depression. The other two [18,57] did not observe any affective alteration following 12 and 24 weeks, respectively.…”
Section: Studies Applying Strength Trainingmentioning
confidence: 99%
“…In 11 RCTs wurden primär Effekte eines körperlichen Trainings bei älte-ren Menschen mit klinischer Depression [12,19,54,73,74,76] oder mit depressiver Symptomatik ermittelt [13,18,72], in 2 Studien wurden gemischte Populationen untersucht [64,84]. Von den 11 RCTs weisen 8 positive Effekte eines Trainings auf (.…”
Section: Kann Körperliches Training Depressionen Verringern?unclassified
“…2; [12,13,19,64,73,74,76,84]). Bei 3 RCTs konnten keine signifikanten Verbesserungen der Depression erzielt werden [18,54,72].…”
Section: Kann Körperliches Training Depressionen Verringern?unclassified
See 1 more Smart Citation